The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1128/aac.04446-14
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Effects of Echinocandins after Central Venous Administration in Adult Rats

Abstract: Echinocandins have become the agents of choice for early and specific antifungal treatment in critically ill patients. In vitro studies and clinical case reports revealed a possible impact of echinocandin treatment on cardiac function. The aim of our study was to evaluate echinocandin-induced cardiac failure. Using an in vivo rat model, we assessed hemodynamic parameters and time to hemodynamic failure after central venous application (vena jugularis interna) of anidulafungin (lowdose group, 2.5 mg/kg body wei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
18
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 28 publications
4
18
0
1
Order By: Relevance
“…Regarding the LDH serum levels of our in vivo rat studies, we only found a trend toward elevated LDH values in anidulafungin-treated animals compared to that in control group animals. These results are in line with data form previous studies that did not observe micafungin-induced cardiac impairment (10)(11)(12)(13). This fact may be explained by the hypothesis that micafungin, which is water-soluble compared with the other two lipophilic agents, would be unable to penetrate the tissue and cause serious cell damage.…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…Regarding the LDH serum levels of our in vivo rat studies, we only found a trend toward elevated LDH values in anidulafungin-treated animals compared to that in control group animals. These results are in line with data form previous studies that did not observe micafungin-induced cardiac impairment (10)(11)(12)(13). This fact may be explained by the hypothesis that micafungin, which is water-soluble compared with the other two lipophilic agents, would be unable to penetrate the tissue and cause serious cell damage.…”
Section: Discussionsupporting
confidence: 82%
“…Hemodynamic measurements after central venous administration of high doses of anidulafungin or caspofungin in adult rats provided evidence of significantly reduced cardiac output, which was associated with a significantly reduced survival rate compared to that in control animals (12). These results, which suggest a dose-depending mechanism of echinocandin-induced cardiac depression, were also confirmed by a study of rats treated with different doses of echinocandins (13).…”
supporting
confidence: 73%
See 3 more Smart Citations